MIDDLE TRIASSIC BRACHIOPODS FROM VAL PARINA, BERGAMASC ALPS, ITALY (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The Middle Triassic Esino Limestone of Val Parina yields a rich brachiopod fauna associated with bivalves, gastropods, corals, and ammonoids. The brachiopod fauna of the Esino Limestone includes ubiquitous species (P. fragilis, A. aff. posterior, M. mentzeli, D. cf. dinarica, L. praepunctata and A. angustaeformis), species exclusive to the back reef (T. cf. intervallata, A. aff. ladina and A. aff. raxana) and species exclusive to the shelf margin (C. aff. altaplecta, V. vivida, A. aff. dilatata, H. aff. ambitiosa, T. trigonella, M. ampla, A. aff. canaliculata). The age of the Val Parina brachiopods spans from latest Anisian to Late Ladinian.